Reading Brains. - Klarreich, Erica (Communications of the ACM, 2014)
The article discusses the study of brain-decoding algorithms to develop brain-machine interfaces, or mind-reading research, as of March 2014, with a focus on a study by Marcel van Gerven of Radboud University Nijmegen in Nijmegen, Netherlands to be printed in the journal "Neuroimage." The study's use of functional magnetic resonance imaging (fMRI) machines to measure responses from the primary visual cortex (V1) is discussed. Comments from Jack Gallant, neuroscientist at the University of California, Berkeley in Berkeley, California, are also included.